The Effect of Substituents on the Properties of Porphyrin and metalloprophyrin Semiconductors Using Density Functional Theory - Ashraq T. Atwan; Mohammed L. Jabbar (Genius Journals, 2022)
A few porphyrins and their metal complex (metalloporphyrin) assume huge parts in detecting, photodynamic treatment, attractive reverberation imaging (MRI), anticancer medications, electronic gadgets, and fluorescence imaging. In this work, the impact of changing the focal metal was thought about, as titanium metal and cadmium metal were utilized. As well as adding chlorine atom to the focal metal, as well as concentrating on the impacts of various closures of the compound, once by making hydrogen at the mesocloses and again by making phenyl rings at the meso-closes. Furthermore, information on all past impacts on electronic properties and their improvement. For instance, the energy of filled and HOMO and LUMO, the energy gap, hardness, delicate quality compound electronegativity, and electrophilicity are determined. It very well may be seen that the chose materials have a lower energy gap than the pure porphyrin. The energy gap of the mixtures examined, which are all situated in the semiconducting locale (1.109352 - 2.91692 eV), can thusly be utilized in significant electronic applications like sensors, transistors and solar cells. All computations were done with the Gaussian 09 programming package.
Keywords: Porphyrin; Density Functional Theory; Energy Gap